KOSAKATA TATA BOGA TRADISIONAL DALAM BAHASA DAYAK BAKATI’ SUBAH - Heni Yusnita; Hotma Simanjuntak; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the culinary vocabulary in the Dayak Bakati' language. The culinary vocabulary was studied in the form of vocabulary, lexical meaning, grammatical meaning, cultural meaning, and implementation of Indonesian language learning. The method used in this research is descriptive. The form of research is qualitative. Sources of data are native speakers of the Dayak Bakati' tribe and research data are traditional food and drinks. Data collection techniques are listening techniques, speaking techniques, note-taking techniques, and recording techniques. This study resulted in 62 traditional Dayak Bakati' Subah culinary vocabularies with the classification of 35 vocabularies for staple food, 5 for drinks, 7 for snacks, 10 for making ingredients, and 5 for the manufacturing process. 20 monomorphemic vocabularies of staple foods, 4 vocabularies of drinks, 5 vocabularies of snacks, 8 vocabularies of ingredients, polymorphemics in the form of food 11 vocabularies of staple foods, 2 vocabularies for drinks, 4 vocabularies in the form of affixes, and 3 forms of Indonesian language learning texts based on traditional culinary vocabulary in the Dayak Bakati language, it produces learning texts, namely procedure texts.Keywords: Vocabulary, Catering, Traditional, Dayak Bakati' Subah